The Effect of Flipbook Media on Early Reading Skills in Early Childhood - Agna Tri Putri; Aida Imtihana; Indah Dwi Sartika (Universitas Sebelas Maret, 2026)
This study was motivated by the low early reading skills of young children. This study aims to determine whether the use of flipbooks affects children’s early reading skills. This study employed a quantitative method using a One-Group Pretest-Posttest Design. The study sample consisted of 21 children in Group B. Data collection techniques included observation, documentation, and testing, while data analysis utilized a paired-sample t-test with the assistance of SPSS software. The results of the study indicate an improvement in early reading skills following the use of the flipbook medium. This is evidenced by a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant effect of the flipbook medium on the early reading skills of young children at the Darul Jannah.